SOCIO-PSYCHOLOGICAL FEATURES OF LONELINESS IN MODERN TEENAGERS - N. P. Dedov; O. A. Komissarova (Вестник университета)
Relevant socio-psychological problem of the emergence of loneliness in modern adolescents has been considered. Living conditions at this moment are characterized by a high level of development of information technologies. As a result, the formation of new thinking, new behavioral strategies, which affect the process of socialization of the individual. It has been noted, that in connection with the intensive digitalization of society, prerequisites arise for the social isolation of an individual subject, the formation of loneliness. This is most evident in the younger generation, as it is more sensitive to social changes. For exploring this phenomenon, an empirical study was conducted of the attitude of adolescents to loneliness and its interrelation with communicative abilities. Psychodiagnostic techniques have been used as research methods: the UCLA solitude scale by D. Russell, L. Peplo, M. Ferguson and the CBS questionnaire. For a quantitative analysis of the obtained data, the Spearman rank correlation coefficient has been used. An analysis of the results allowed us to establish the presence of loneliness in modern adolescents, which is associated with a decrease in their communicative abilities. The results can be used in the practical activities of social psychologists, teachers and educators.